The Role of Halal Certification in Enhancing Competitiveness and Social Trust: A Study on the Culinary Industry in Surabaya - Della Rista Pratiwi; Zanuba Fristya; Auria Dwi Putri (Universitas Negeri Surabaya, 2025)
This research aims to analyze the role of halal certification in enhancing competitiveness and social trust in the culinary industry of Surabaya. Halal certification is considered essential in addressing the needs of Muslim consumers, who increasingly prioritize the halal aspects of products. Using a mixed-methods approach, this study involves in-depth interviews with culinary entrepreneurs, consumers, and experts in halal certification. The findings reveal that halal certification not only serves as a guarantee of product halalness but also contributes to building a positive reputation and image for businesses. Furthermore, the presence of halal certification increases consumer trust, which in turn impacts loyalty and boosts sales. The research also identifies the challenges faced by entrepreneurs in obtaining halal certification, along with strategies that can be implemented to overcome these obstacles. These findings are expected to provide insights for culinary industry players and policymakers on leveraging halal certification as a tool to enhance competitiveness and build social trust in the market.